A Great Leap Forward, the Second Time Around: Thirty Years of Economic Reforms in China - Alfred Steinherr (Weekly Report, 2009)
December of 2008 marks the 30th year of the beginning of China's economic opening. The country's rapid development since 1978 is without historical precedent. Yet this growth is even more impressive when one surveys the entire period from the founding of the People's Republic in 1949 to present. Although the years from1949 to 1978 were close to catastrophic, and the basis for economic development over the next thirty years could have hardly been worse, on the 60th anniversary of the government's founding, the country's achievements - at least from an economic perspective - must be viewed as an extraordinary success. On the 30th anniversary of China's economic opening, the following article assesses that which has been achieved to date. It also explores the causes of the economic stagnation of the "lost decades" between 1949 and 1978. The deep stagnation experienced during the early years of the People's Republic as well as China's reorientation in 1978 and subsequent boom can only be understood with reference to this historical period. Any assessment of the country's present-day political and economic situation is also contingent upon an appreciation of the long cycles that characterize Chinese history. Since the opening of the country and its rise to the world's second-largest economy and trading partner, China has surpassed Japan and taken on equal standing with the EU as the most significant decision maker in economic and political affairs after the US. China's importance is not yet reflected in World Bank and IMF quotas or in the composition of the G8-yet China is sure to take on an increasingly prominent role in coming years. If China can maintain the growth rates witnessed over the past three decades, in less than 15 years it will surpass the US as the world's largest economy and most significant trading partner. While the future is by no means preordained, all of the preconditions for this to occur are in place. China still possesses large labor reserves; is a net creditor to the rest of the world and holds currency reserves of a historically unprecedented volume; will soon be the largest and most dynamic domestic market in the world (and will therefore continue to attract direct foreign investment); and displays considerable potential for growth in domestic demand. Furthermore, the reform of China's financial sector and the deregulation of capital flows could potentially stoke additional economic expansion. The current financial crisis has not left China unscathed, but is unlikely to have a lasting effect on the country's long-term development.
Keywords: O10; O53; P27; 330; China; Communism; Market Economy; Gradualism